2019
DOI: 10.1093/infdis/jiz629
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Zika Virus Findings in Twin Pregnancies Complicated by Antenatal Zika Virus Exposure: A Prospective Cohort

Abstract: Background There are limited data on the natural history of antenatal Zika virus (ZIKV) exposure in twin pregnancies, especially regarding intertwin concordance of prenatal, placental, and infant outcomes. Methods This prospective cohort study included twin pregnancies referred to a single institution from September 2015 to June 2016 with maternal ZIKV. Polymerase chain reaction (PCR) testing of maternal, placental, and neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…A series of ZIKV affected twin pregnancies have been reported in the literature, some with concordant and others with discordant outcomes. Twin discordance seems to be a more common finding among dizygotic (DZ) pregnancies, and it can be seen at multiple levels including within clinical and laboratory findings between the twins, between the placentas or the portions of a single placenta, and between the infant and corresponding placenta [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A series of ZIKV affected twin pregnancies have been reported in the literature, some with concordant and others with discordant outcomes. Twin discordance seems to be a more common finding among dizygotic (DZ) pregnancies, and it can be seen at multiple levels including within clinical and laboratory findings between the twins, between the placentas or the portions of a single placenta, and between the infant and corresponding placenta [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further analysis that included in vitro ZIKV infection of neural progenitor cells (NPCs) derived from human induced pluripotent stem cells from three pairs of discordant DZ twins identified a significant difference of NPC survival and viral replication being more severe in samples from the affected twin of each pair [ 34 ]. Most of the reported cases of MZ twin pregnancies with congenital ZIKV infection have concordant clinical outcomes, either having absence of adverse outcomes [ 32 ] or compromise in both fetuses/infants [ 34 , 35 ]. For DZ and MZ pregnancies with concordant fetal and infant outcomes, the extent of the clinical compromise can be variable, including differential findings regarding CNS and eye abnormalities and of neurodevelopmental sequelae such as epilepsy, developmental delay, and hearing loss [ 32 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…twin should be evaluated independently for vertical transmission [34]. In this scenario, discordant twins represent a good case-control sample to test for the genetic contribution determining the fetuses' discordant outcome of gestational infection with ZIKV, as they are supposed to have been exposed to ZIKV under similar conditions in the uterus during gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, neural progenitor cells (NPCs) from different individuals have been shown to respond differently to ZIKV infection [ 32 , 33 ]. It has recently been shown that infant outcomes can be discordant between twins with prenatal ZIKV exposure, suggesting that each twin should be evaluated independently for vertical transmission [ 34 ]. In this scenario, discordant twins represent a good case–control sample to test for the genetic contribution determining the fetuses’ discordant outcome of gestational infection with ZIKV, as they are supposed to have been exposed to ZIKV under similar conditions in the uterus during gestation.…”
Section: Introductionmentioning
confidence: 99%